Creating Capitalism: Politics, Reforms, and Economic Performance - Frank Wykoff (Claremont McKenna College, Department of Economics, 2001)
Building on a model that integrates reforms into exogenous and endogenous growth models, this paper designs an econometric model of the interplay between economic reform measures, political decisions and economic performance. Several key hypotheses about transition are tested using two-stage least squares on a logit model using data for six countries (Bulgaria, the Czech Republic, Estonia, Hungary, Russia and Slovakia) over their first ten years of freedom. We draw three conclusions from the empirical evidence. (1) Contrary to the litany that everyone favors reforms, we find that voting for strong reform parties leads to more reforms. (2) History matters, even in a model of forward looking rational agents. Where communism was relatively popular, Russia, Hungary and Bulgaria, reform is slower, more problematic, and aimed toward a welfare state not US-style capitalism. The cost of debunking communist ideology evidently slows progress considerably. (3) Better economic performance does not result quickly from reforms. From a public choice perspective the immediate identifiable social costs of reforms often appear stronger than the eventual diffuse benefits. Though not surprising this result does not auger well for reformers. Finally, critical macroeconomic data for the earlier years around the transition period are very poor quality. Indeed economic data seems to be too poor to reveal much about changing economic circumstance. Measured output may actually move in the opposite direction of realized output. International agencies could contribute greatly to analysis of transition by quickly and deeply engaging the local statistical agencies.
Keywords: D72; O52; C32; C35; P16; P17; 330; transition; reforms; growth; voting; public choice; Central Europe; Russia; two stage least squares; logit